Structural Characterization of ZS – 2A: An Antiplasmodial Compound Isolated from Zizyphus spina-christi Root Bark - Adzu, Bulus; Haruna, Abdu Kaita; Ilyas, Mohammad; Pateh, Umar Usman; Tarfa, Florence David; Chindo, Ben Ahmed; Gamaniel, Karniyus Shingu (Journal of Pharmacy and Nutrition Sciences, 2022)
Zizyphus spina-christi (Rhamnaceae) is a popular medicinal plant that grows wildly in Asia and Tropical Africa. The plant is widely used in ethnomedical practice for the treatment of fever. As a step towards the isolation of biologically active constituents of this plant, we carried out a bioassay guided extraction of the root bark using solvents of varying polarity including, hexane, chloroform, ethylacetate and methanol. An antiplasmodial compound, designated as ZS-2A, was isolated from the chloroform extract and the chemical structure of the compound was characterized using UVvisible, IR, 13C and 1H NMR and thermo-analytical techniques. Our analysis established ZS – 2A as a betulinic acid.